-3x+4=5x-3

Simple and best practice solution for -3x+4=5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+4=5x-3 equation:


Simplifying
-3x + 4 = 5x + -3

Reorder the terms:
4 + -3x = 5x + -3

Reorder the terms:
4 + -3x = -3 + 5x

Solving
4 + -3x = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
4 + -3x + -5x = -3 + 5x + -5x

Combine like terms: -3x + -5x = -8x
4 + -8x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
4 + -8x = -3 + 0
4 + -8x = -3

Add '-4' to each side of the equation.
4 + -4 + -8x = -3 + -4

Combine like terms: 4 + -4 = 0
0 + -8x = -3 + -4
-8x = -3 + -4

Combine like terms: -3 + -4 = -7
-8x = -7

Divide each side by '-8'.
x = 0.875

Simplifying
x = 0.875

See similar equations:

| 4x-16y=-44 | | 28-7x=3x-12 | | -8x+28=-4x+56 | | 6y-3=2y-15 | | (4x-1)/(3x)4x | | 23x-4=180 | | 8/7=3/3b | | 23x-4+4x-1+9x-31=180 | | 8r=45 | | .5(x-10)=7 | | 19x-6+4x=180 | | x^2+y^2-10y+25=36 | | x=yx | | 5y+3=42 | | f-32/1.8 | | 12x-1/2x^=0 | | 7n+5=58 | | (1.8*C)+32= | | 16x-27=180 | | 5f+s=t | | (4d+3)*(4d-3)= | | (1.8xC)+32= | | -17x-11=-62 | | 1.176471x=100+.08(1.176471)x | | 83=4w+15 | | 12-6m=6m+60 | | [n+4]=11 | | -7x-3=0 | | 4ex=24 | | 2a^2-9a=81 | | n^2-5n+6n-51=0 | | 4 = t27 |

Equations solver categories